Study on the depth reduction of concrete beam using mega mesh polypropylene fibres under flexural load - Cheah, Kar Jun (2015)
Nowadays, rapid development in construction uses a lot of concrete as building materials. While during producing concrete, it causes certain problem which will cause environment pollution. Beside that deep beam will decrease the clear height of the floor due to the space allocation used up for the ceiling to cover the beam. This research deals with the effect of additional mega mesh polypropylene fibre (MMPF) on the depth reduction of concrete beam. The objective of this research was to find out the flexural strength of MMPF concrete beam and the optimum depth can be achieved by MMPF in strengthening flexural strength of the concrete. This research first is to prepare the concrete with grade M30 and additional fibre in different depths of 100mm, 90mm, 80mm, 70mm, 60mm, 50mm and a control beam without fibre with 100mm depth for flexural test. While cylinder concrete with fibre and without fibre were cast to determine for compressive strength and elastic modulus properties. Based on the strength and the statistical analysis conducted on the tested specimens. The addition of mega mesh polypropylene fibres in concrete shows an increase in flexural load able to be sustained by the concrete. The inclusion of MMPF in fresh concrete decreased the workability up to 19.52% lower than plain concrete, however addition of MMPF was able to increase the compressive strength up to 57.13% higher than plain concrete. The elastic modulus also shows 54.08% increment as compared to control. Based on the result, the optimum depth can be achieved by MMPF to improve flexural strength of concrete beam was 90mm. Therefore, the addition of MMPF in concrete beam has a good potential as one of the depth reduction variable in concrete beam.